Energy crisis and companies’ investment in renewable energy sources: case of Metal Processing Cluster - Przygodzka, Renata; Trocka, Natalia (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Improving the energy efficiency of enterprises is now not only a postulate of inter-national and national energy transition strategies towards climate neutrality, but also a requirement for maintaining their profitability and competitive capacity. Rising energy fuel prices and the unstable geopolitical situation, and above all, the war in Ukraine, are causing many enterprises to take energy-saving actions (ESA’s). One of them is investing in renewable energy sources (RES) for their own consumption, understood as investing in future energy purchase savings. Aim: The article aims to identify the involvement of enterprises affiliated with the Metal Processing Cluster (MPC), which has the status of the Polish Key National Cluster, in RES investments in the context of the energy crisis. It also attempts to verify the hypothesis: greater interest in investing in RES is shown by enterprises that have seen a strong negative impact of energy price increases on their operations. The research was carried out on the basis of literature studies, analysis of Polish Central Statistical Office statistical data and analysis of reports of various institutions. Empirical verification of the hypothesis was possible on the basis of the results of surveys conducted in the enterprises of the MPC. Results: The research showed that in 2022, more than half of the surveyed companies affiliated with the MPC felt the negative (very strong and strong) effect of rising energy prices. It primarily had an impact on the decline in their profitability. In 73% of the surveyed companies, this situation influenced the decision to start investments in renewable energy sources, with the majority of these investments being in photovoltaic panels. The survey contributes to the knowledge of the impact of the energy crisis on RES investments in metal companies.